Impact of the COVID-19 pandemic on Physical Activity and Student Achievement - Alan Alfiansyah Putra Karo Karo; Dimas Arif Hidayat; Ricky Fernando Pasaribu; Firdo Aginta Silalahi; Liliana Puspa Sari (JUARA : Jurnal Olahraga, 2022)
This COVID-19 pandemic situation is considered unfavourable for some parties due to several factors such as restrictions on activities outside the home and sometimes feeling overwhelmed with many tasks while at home. So the purpose of this research is to see the impact of the Covid-19 pandemic on physical activity and student achievement. The subjects in this study were students who voluntarily filled out a questionnaire distributed through social media. A total of 124 respondents were collected. The 124 students were divided into five categories of levels of physical activity. There are 26 students in the shallow category, 67 students in the low class, 23 in the medium category, eight students in the high sort and 0 in the very high category. The intensity of physical activity during the pandemic in a week shows five students do not do physical activity at all a week, 74 students do one physical activity a week, 25 students do 2 or 3 times physical activity a week, ten students do 4 or 5 times physical activity a week, and ten students do 6 or 7 times of physical activity in a week. While the student achievement of 124 students seen as many as 98 students are in a complete category or the percentage of 79.03%, and as many as 26 students are in the incomplete category or the rate of 20.97%. The average value of student learning outcomes in physical education subjects is 80.60. Based on the study results, it can be concluded that students' physical activity during the COVID-19 period was included in the low category with an intensity level of physical activity once a week. The student achievement is at a high level of completeness